Sources and aging of individual atmospheric particles in New York City Integrating novel functional group data from optical photothermal spectroscopy with elemental and mass spectrometry data - Xiao, Yao (Aerosol science and technology : the journal of the American Association for Aerosol Research, 2025)
Elevated concentrations of fine particulate matter (PM2.5, particles < 2.5 μm) lead to negative health outcomes in urban areas, such as New York City (NYC). The sources of particles contributing to PM2.5 in NYC are variable and complex due to the range of primary anthropogenic and biogenic emissions, as well as secondary aerosol formation (i.e., aging) from gaseous precursors. To improve understanding of the contributors to PM2.5, single particle microspectroscopy uses chemical fingerprints to identify sources and the extent of aging, but few studies have integrated multiple microspectroscopy methods to understand PM2.5 in NYC. Herein, we focus on a recently-developed form of microspectroscopy that can measure atmospherically-sized particles (>~0.8 μm), optical photothermal infrared (O-PTIR). We compare O-PTIR to existing microspectroscopy methods [Raman, fluorescence, and energy dispersive X-ray (EDX)] to study sources and aging of the complex NYC aerosol based on functional group and elemental information, which we also relate to bulk mass spectrometry methods. Single particle data shows submicron aerosol composition dominated by carbonaceous particles that fluoresce mixed with ammonium and sulfate, with a range of oxidized organic functional groups observed. At larger sizes, more primary sources (salts, dust, and biological) were observed, with nitrate being the dominant secondary anion. Collectively, the results from OPTIR and other instruments across case-study days reveal variations in sources and aging, with greater variability at larger diameters. Demonstrating the potential of O-PTIR when combined with the other methods to provide data that is important for improving air quality in urban megacities